Dynamic-SoS: An Approach for the Simulation of Systems-of-Systems Dynamic Architectures. (12th April 2019) - Manzano, Wallace; Graciano Neto, Valdemar Vicente; Nakagawa, Elisa Yumi
Abstract: Systems-of-Systems (SoS) combine heterogeneous, independent systems to offer complex functionalities for highly dynamic smart applications. Besides their dynamic architecture with continuous changes at runtime, SoS should be reliable and work without interrupting their operation and with no failures that could cause accidents or losses. SoS architectural design should facilitate the prediction of the impact of architectural changes and potential failures due to SoS behavior. However, existing approaches do not support such evaluation. Hence, these systems have been usually built without a proper evaluation of their architecture. This article presents Dynamic-SoS, an approach to predict/anticipate at design time the SoS architectural behavior at runtime to evaluate whether the SoS can sustain their operation. The main contributions of this approach comprise: (i) characterization of the dynamic architecture changes via a set of well-defined operators; (ii) a strategy to automatically include a reconfiguration controller for SoS simulation; and (iii) a means to evaluate architectural configurations that an SoS could assume at runtime, assessing their impact on the viability of the SoS operation. Results of our case study reveal Dynamic-SoS is a promising approach that could contribute to the quality of SoS by enabling prior assessment of its dynamic architecture.